The Foundations of Ethnic Politics: Separatism of states and Nations in Eurasia and the World - Hale, Henry E (Cambridge University Press, 2013)
Despite implicating ethnicity in everything from civil war to economic failure, researchers seldom consult psychological research when addressing the most basic question: What is ethnicity? The result is a radical scholarly divide generating contradictory recommendations for solving ethnic conflict.Research into how the human brain actually works demands a revision of existing schools of thought. At its foundation, ethnic identity is a cognitive uncertainty-reduction device with special capacity to exacerbate, but not cause, collective action problems. This insight leads to a new general theory of ethnic conflict and nationalism that can improve both understanding and practice. Supporting this claim is a wide-ranging discussion of patterns in secessionism, international integration, state collapse, race relations, and deadly ethnic violence found across the globe. Special attention is paid to an in-depth case study of national separatism in Eurasia, which produces a major reinterpretation of nationalism’s role in the USSR’s breakup and interstate relations in the Commonwealth of Independent States.